Manajemen Strategi Pemasaran Pendidikan Di SDIT Alam Nurul Islam Sleman - Jamaludin (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
This research puspose was to know the concrete management education marketing strategies in SDIT Alam Nurul Islam. This study used qualitative method to observe and analyze the education marketing service and the applied management in the school. The data was collected from the interview results, documentation and study on the observation subjects. Then it was processed with the descriptive analytic approach and presented in narration. The research results was show that: (1) Education marketing strategies by promoting the school model/concept was considered to be good; the segmentation that being targeted are the middle and high level education persons. (2) The effectiveness of promotion media such as conventional and unconventional media; included the word of mouth technique (gethok tular, Javanese language); (3) Marketing strategies management during the initial stages are making banners, presentation to the pre-school institution, and so on; in the next stage are depend on the internet based media; and in the next phase are set to make sustainable promotion media like a merchandise.